Towards serving the mankind: The role of the Ramakrishna mission and human development in India - Mitra, Karabi (2014)
In Indian tradition religious development of a person is complete when he experiences the world within himself.The realization of the existence of the omnipresent Brahman --- the Great Spirit is the goal of the spiritual venture. Gradually traditional Hinduism developed negative elements born out of age-old superstitious practices. During the nineteenth century changes occurred in the socio-cultural sphere of colonial India. Challenges from Christianity and Brahmoism led the orthodox Hindus becoming defensive of their practices.Towards the end of the century the nationalist forces identified with traditional Hinduism.Sri Ramakrishna, a Bengali temple-priest propagated a new interpretation of the Hindu scriptures.Without formal education he could interpret the essence of the scriptures with an unprecedented simplicity.With a deep insight into the rapidly changing social scenario he realized the necessity of a humanist religious practice. He preached the message to serve the people as the representative of God.In an age of religious debates he practiced all the religions and attained at the same Truth.Swami Vivekananda, his closest disciple carried the message to the Western world.In the Conference of World religions held at Chicago (1893) he won the heart of the audience by a simple speech which reflected his deep belief in the humanist message of the Upanishads.Later on he was successful to establish the Ramakrishna Mission at Belur, West Bengal. He initiated a religious movement with the sole aim and objective being the dedicated service to the humanity.At present the Ramakrishna Mission with its branches all over the world serves the cause of humanity, contribute to the dissemination of the man-making mission propagated by Swamiji and represent the spirit of Indian culture in the world. The paper will address how Swamiji inaugurated a humanist movement amidst numerous challenges and was successful to leave a progeny of saffron-clad monks dedicated to the well being of the mankind.